Bullous keratopathy associated with a shallow anterior chamber: An anatomical risk phenotype for corneal endothelial decompensation - Masato Takeda; Yuki Mizuki; Ami Igarashi; Toshiki Shimizu; Naoki Okumura; Nobuhisa Mizuki; Satoru Yamagami; Takahiko Hayashi (PLoS ONE, 2026)
Purpose To characterize bullous keratopathy (BK) associated with a shallow anterior chamber (AC) and to examine whether a shallow AC itself may be associated with corneal endothelial decompensation, even in the absence of acute primary angle closure (APAC) or argon laser iridotomy (ALI). Methods This multicenter retrospective observational study included 96 eyes that underwent Descemet membrane endothelial keratoplasty (DMEK) for endothelial dysfunction between 2015 and 2025 with ≥12 months of follow-up. The primary comparative analyses compared eyes with Fuchs endothelial corneal dystrophy (FECD) and eyes with endothelial dysfunction associated with a shallow AC. The shallow anterior chamber phenotype group comprised eyes with a documented history of APAC or ALI (PACD/ALI) and those without a documented history of either condition (shallow-AC). Anterior chamber depth (ACD), axial length, corneal thickness, endothelial parameters, and postoperative outcomes were compared between groups. Results Pre-cataract ACD was significantly shallower in the shallow anterior chamber phenotype group than in the FECD group (1.93 ± 0.40 mm vs. 2.28 ± 0.27 mm, P < 0.001), and this relative difference persisted after cataract surgery. Within the shallow anterior chamber phenotype group, 10 eyes were classified as shallow-AC and had no documented history of APAC or ALI. Five-year graft survival after DMEK exceeded 90% and did not differ significantly between the shallow anterior chamber phenotype and FECD groups, nor between PACD/ALI and shallow-AC subgroups. Conclusions A shallow anterior chamber may be associated with corneal endothelial decompensation, even in the absence of APAC or ALI. With appropriate perioperative management, DMEK may provide favorable long-term outcomes in these eyes.